Weaning calves early from drylot - McKee, M.; Fink, G. (Kansas State University. Agricultural Experiment Station, 2011)
Percentage Simmental and Hereford calves gained slightly more (13 lbs./hd) while nursing their mothers than 83 herd mates that were weaned early at 49 (+27) days of age. Percentage Simmental cows whose calves were weaned early had a higher conception rate than percentage Simmental cows that nursed calves (93% vs. 89%) Dams of calves weaned early rebred 17.6 days sooner than nursing dams.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Weaning calves; Drylot; Conception rate